2020
DOI: 10.1101/2020.06.13.149658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain-predicted age associates with psychopathology dimensions in youth

Abstract: Background: This study aims to investigate whether dimensional constructs of psychopathology relate to advanced, attenuated or normal patterns of brain development, and to determine whether these constructs share common neurodevelopmental profiles.Methods: Psychiatric symptom ratings from 9312 youths (8-21 years) were parsed into 7 independent dimensions of clinical psychopathology representing conduct, anxiety, obsessivecompulsive, attention, depression, bipolar, and psychosis symptoms. Using a subset of this… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…As with previous studies in this cohort, we did not find strong evidence of association between brain age delta and cognitive performance, after accounting for age and sex [Ball et al, 2017;Khundrakpam et al, 2015]. Other studies have reported small to moderate associations between brain age and measures of cognitive performance during typical development [Erus et al, 2015;Lewis et al, 2018], or associations between brain age estimates and symptoms of psychopathology or neurodevelopmental disorders [Cropley et al, 2020;Tunç et al, 2019]. Our findings do not preclude the detection of brain age-behaviour associations in typically-developing samples, others have employed multi-modal approaches to successfully predict brain age from brain structure and function, additionally using measures of tissue microstructure from diffusion MRI and subcortical metrics rather than just cortical thickness and area [Erus et al, 2015;Lewis et al, 2019;Liem et al, 2017].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…As with previous studies in this cohort, we did not find strong evidence of association between brain age delta and cognitive performance, after accounting for age and sex [Ball et al, 2017;Khundrakpam et al, 2015]. Other studies have reported small to moderate associations between brain age and measures of cognitive performance during typical development [Erus et al, 2015;Lewis et al, 2018], or associations between brain age estimates and symptoms of psychopathology or neurodevelopmental disorders [Cropley et al, 2020;Tunç et al, 2019]. Our findings do not preclude the detection of brain age-behaviour associations in typically-developing samples, others have employed multi-modal approaches to successfully predict brain age from brain structure and function, additionally using measures of tissue microstructure from diffusion MRI and subcortical metrics rather than just cortical thickness and area [Erus et al, 2015;Lewis et al, 2019;Liem et al, 2017].…”
Section: Discussionsupporting
confidence: 69%
“…In children with autism spectrum disorder, a negative brain age gap (reflecting that the brain was predicted to be younger than expected for chronological age) was related to greater disorder symptom severity [Tunç et al, 2019]. In a non-typically developing sample of children and adolescents, a positive brain age gap was associated with greater psychopathology symptom severity [Cropley et al, 2020].…”
Section: Introductionmentioning
confidence: 97%
“…The present study included 1313 participants (mean age 14.5 years, SD = 3.43, 659 F) for whom a structural magnetic resonance imaging (MRI) scan was acquired. This sample was obtained after excluding participants on the basis of image quality, medical conditions, and missing data (n = 285; for details see Cropley et al, 2020 ). Structural MRI scans from this final PNC sample were used to train the normative brain age model described in subsequent sections.…”
Section: Methodsmentioning
confidence: 99%
“…Using data from the PNC sample, a support vector regression (SVR) model (using 10-fold cross-validation) was used to predict each individual’s age (in the PNC sample) based on the 111 measures listed above (i.e., the normative model; Cropley et al, 2020 ). All measures were standardized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation